(untitled) (LIS TODAY, 2025)
This study investigates user satisfaction with library resources and Information and Communication Technology (ICT) based services at Magadh University, Bodh Gaya, Bihar, India. The research employs survey research method, combining structured questionnaire to assess the effectiveness of library services and resources. A sample of 500 students and faculty members participated in the study. Results indicate a moderate level of satisfaction with traditional library resources but highlight significant gaps in ICT-based services. The study recommends strategic improvements in digital resources, ICT infrastructure, and user training to enhance overall user satisfaction and library effectiveness.